Hadron-quark phase transition at nonzero isospin density: the effect of quark pairing - Pagliara, Giuseppe; Schaffner-Bielich, Jürgen (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We compute the mixed phase of nuclear matter and 2SC matter for different temperatures and proton fractions. After showing that the symmetry energy of the 2SC phase is, to a good approximation, 3 times larger than the one of the normal quark phase, we discuss and compare all the properties of the mixed phase with a 2SC component or a normal quark matter component. In particular, the local isospin densities of the nuclear and the quark component and the stiffness of the mixed phase are significantly different whether the 2SC phase or the normal quark phase are considered. If a strong diquark pairing is adopted for the 2SC phase, there is a possibility to eventually enter in the nuclear matter 2SC matter mixed phase in low energy heavy ions collisions experiments. Possible observables able to discern between the formation of the 2SC phase or the normal quark phase are finally discussed.